Colonized Body Of Women In Ahmad Tohari’s Novel The Dancer - Zita Rarastesa (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study aims to analyze how the female body is colonized in Ahmad Tohari's novel "The Dancer." The novel portrays the lives of women in Javanese culture, shaped by colonialism and patriarchy, and illustrates how the female body becomes a site of domination, control, and exploitation. Utilizing a postcolonial feminist perspective, this research examines the experiences of physical, psychological, and social oppression faced by the female characters in the novel and their responses to various forms of colonization of their bodies. The findings reveal that through narrative and characterization, Ahmad Tohari explores the complexities of female identity influenced by colonial history and patriarchal structures. These findings highlight the importance of understanding the female body as a battleground between dominant forces and women's resistance against various forms of oppression. Thus, this study contributes to the broader discourse on gender and colonialism studies in Indonesian literature.